THE IMPLEMENTATION OF DIFFERENTIATED READING INSTRUCTION IN EFL CONTEXT: STRATEGIES, IMPACTS, AND CHALLENGES - Rukadah, Rukadah; Priyana, Joko; Hidayati, Sari (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2025)
This study is conducted using a systematic literature review which explores the strategies, impacts, and challenges during the implementation of Differentiated Reading Instruction (DRI) strategies in English as a Foreign Language (EFL) Classrooms.  The literature review analyses 19 studies published between 2014 and 2024, sourced from databases like Scopus, Google Scholar, and Mendeley. The findings reveal that tiered assignments and flexible grouping achieve the highest frequency use in DRI implementation. The strategies show the positive effects namely on reading comprehension, student engagement, and self-confidence. However, the reviews also find out the challenges such as a restricted time, limited resources, and insufficient teacher training hinder effective implementation. For further research, it is recommended to explore on other language skills namely listening, speaking, and writing to broad the impacts of DRI. The study also identifies the importance of teachers’ training on DI practices to overcome the challenges in diverse classrooms.